Catfish Budikdamber Business Development Strategy Using QSPM and MAUT Model in Bandar Kidul District, Kediri City - Asyifa Anandya; Dwi Sofiati; Pudji Purwanti; Mochammad Fattah; Gama Dian Nugroho; Yunita Erni Susanti (Universitas Islam Lamongan, 2025)
The aquaculture industry in Indonesia faces challenges concerning land availability, especially in areas with limited land resources. The approach involves cultivating fish in buckets (budikdamber) via the aquaponic technology. This study seeks to devise business development strategies and identify priority methods for the advancement of the catfish budikdamber enterprise in Bandar Kidul Village, Kediri City. This research utilizes a descriptive methodology that applies a quantitative approach, integrating both qualitative and quantitative data concurrently (mixed method). This study was executed from July to August 2024 employing a saturation sampling technique. Data were examined utilizing SWOT analysis, QSPM, and the MAUT model. A total of eight methods were successfully designed, encompassing SO, ST, WO, and WT tactics. The outcomes of the QSPM and MAUT Model indicate two priority strategies for the advancement of catfish budikdamber enterprises: enhancing product value through the introduction of processed catfish innovations (ST2) and augmenting sales by incorporating buckets as cultivation containers.